Carbene-Type Species in the Functionalization of Porphyrin Derivatives - Gomes, Ana T. P. C.; Forezi, Luana da S. M.; Simões, Mário M. Q.; Gonzaga, Daniel T.; Cardoso, Mariana F. C.; Da Silva, Fernando de C.; Neves, Maria G. P. M. S.; Ferreira, Vítor F.; Cavaleiro, José A. S. (Synthesis, 2018)
Carbenes and NHCs play an important role in porphyrin chemistry and several synthetically useful transformations leading to the preparation of new porphyrin derivatives have been developed. This short review presents an overview covering the literature from 2007–2017, on the role of these transient species in the functionalization of porphyrin macrocycles.
Keywords: porphyrin; carbene; NHC; cyclopropanation; X–H insertion